Cancer in systemic sclerosis: clinical associations and prognostic impact from the EUSTAR registry - Antonio Tonutti; Francesca Motta; Liala Moschetti; Cosimo Bruni; Carina Mihai; Claudia Iannone; Maria Rosa Pellico; Stefano Stano; Stefano Erba; Claudia Barison; Eleonora Pazzi; Andrea Benini; et al. (Arthritis & Rheumatology, 2026)
Background Cancer represents a major cause of mortality in systemic sclerosis (SSc). Established risk factors are limited to specific subsets, particularly early diffuse anti‐RNA polymerase III (POLR3)‐positive disease, needing further exploration. Methods We performed a nested case‐control study within EUSTAR: cases were SSc patients developing cancer at any timepoint; controls were cancer‐free SSc matched for age and disease duration. Malignancies were classified as synchronous to SSc onset (±3 years), subsequent (>3 years after), or previous (>3 years before). Clinical, serological, treatments associations, and survival were analyzed. Results 454 SSc patients with cancer (29% synchronous, 51% subsequent, 20% previous), and 454 controls were identified. Mean age was 55±13 years, disease duration 5±2 years; 88% were female, 27.5% diffuse SSc; 30.5% had interstitial lung disease (ILD), 32% anti‐topoisomerase, 10% anti‐POLR3. Synchronous cancers were associated with anti‐POLR3 (OR 2.06, 95%CI 1.13‐3.69), U1RNP (OR 3.56, 1.03‐12.3), smoking (OR 1.57, 1.01‐2.44), but negatively with digital ulcers (OR 0.55, 0.31‐0.93). Calcinosis was inversely associated with subsequent cancers (OR 0.42, 0.17‐0.93). Breast cancer showed time‐dependent associations with anti‐POLR3 and anti‐PM/Scl; lung cancer was mainly subsequent and associated with ILD (OR 2.00, 1.12‐3.54), anti‐topoisomerase (OR 2.61, 1.38‐5.04), and smoking. Cancers occurred more frequently in cyclophosphamide‐treated patients. Malignancy worsened overall survival, particularly when subsequent . Radiation therapy did not impact mortality or new‐onset ILD. Conclusions Cancer timing and site identify distinct clinical‐serological associations in SSc, with different prognostic implications. As cancers diagnosed during follow‐up are major determinants of mortality, our findings inform the implementation of stratified cancer surveillance in SSc. image